Endophytic Acremonium kilense as a potential biocontrol agent against leaf blotch disease of clove - Savani, Ajit kumar; Abraham, Koshy; Beena, S (Indian Journal of Plant Protection, 2020)
Endophytic microorganisms (fungi and bacteria) were isolated from leaf samples collected from different agro climatic zones of Kerala state, in order to investigate their biocontrol potential against major foliar pathogens of tree spices (Nutmeg, Clove and Cinnamon). Endophytic fungi isolated from Nutmeg (Myristica fragrans) in the Department of Plant Pathology, College of Horticulture, Vellanikkara have shown promising results. A lab study was conducted to check its antagonist potential against leaf blotch disease of clove and its nonvolatile diffusible metabolites attributes were also tested. The results showed 60 and 64.55 per cent inhibition of clove pathogen, Cylindrocladium quinqueseptatum, in the dual culture and antibiosis assay, respectively.